Arabic and English Loan Words in Bahasa: Implications for Foreign Language Pedagogy - Reima Al-Jarf (Newinera Publisher, 2021)
Many Arab students are currently pursuing their education at Malaysian institutions, and they have to study Bahasa Malaysia as a university requirement to be able to communicate with people in the local community. Therefore, this study aims to help Arab students learn Bahasa easily as Bahasa contains many loan words from Arabic and English. This article gives Arab students examples of Arabic and English loan words with which they are familiar and shows them the different phonological adaptations of Arabic and English loan words in Bahasa as the Arabic, English and Bahasa sound systems are different. A corpus of non-technical Malay words that are commonly encountered in public places in Malaysia was collected and analyzed. A contrastive analysis of Arabic and Malay, and English and Malay phonological systems was performed. Different homogenization processes are applied to Arabic and English loan words depending on the differences between Arabic and Malay, and English and Malay. Examples of Arabic loan words in Malay are: menara, Sabtu, Ahad, Akhir, tahniya. Examples of English loan words in Bahasa are: stesen, kelab, tren, kompleks, imigresen, destinasi. Further implications for learning Bahasa Malaysia by Arab students are given.